Weaving tapestry : collaborative information technology and organisational change - Karsten, Helena (2000)
Collaboration, ongoing working together in a collective, is a significant form of work in modem organisations. Collaborative information technologies are claimed to have been designed to facilitate long-term collaboration in organisations. The goal here is to study how these technologies are intertwined with organisational changes, especially those concerning collaboration. The research draws on a three-year longitudinal qualitative study of a computer consulting company, complemented with several shorter cases and a review of eighteen other major published cases. The empirical work indicated that the crucial role of CIT could be that of a mediator for communication and repository for information. This led to the construction of a theoretical approach, drawing on aspects of Giddens' structuration theory, to understand how emerging collaborative relationships use information and communication and how collaborative information technology use can help or hinder this. The empirical cases also illustrated the very 'social' nature of collaborative information technologies: how the technology supported collaboration and how the users collaborated with it was subject to constant negotiation and modification. Collaborative use of the technology could become established only through construction of sufficiently converging conceptions of the collaborative purposes and possible uses of the applications. Collaborative use required active maintenance, otherwise diverging views on technology and its uses could emerge. This could lead to very different uses of the technology, and consequently exclusion from the user collective. The longitudinal case also provided insight on the nature of changes. In retrospect, change processes formed a complicated pattern that gradually emerged as a result of the situated interaction of the users. When compared to individual changes, collective change appeared to be slow due to the negotiations and individual adjustments required. There also appeared to be considerable periods of latent change, when subtle shifts as a result of individual learning, clarification and maturation of ideas, and innovation, were gradually related to parallel adjustments in other peoples' minds.